INFLUENCE OF RATES AND TERMS OF DEFOLIATION ON THE QUALITY INDICATORS OF SOYBEAN GRAIN (Conferencea, 2023)
This article presents the results of scientific research on the influence of defoliation rates and timing of application on the protein-oil content of early and mid-early soybean varieties planted as a re-crop.